A compound heterozygous ADAMTS13 mutation causes congenital thrombotic thrombocytopenic purpura: a case report - Huang, Yezi; Zhou, Lixia; Song, Yuan; Zou, Wanting; Tang, Aiping; Tao, Si; Tang, Duozhuang (Frontiers in Medicine, 2025)
Congenital thrombotic thrombocytopenic purpura (cTTP) is a thrombotic microangiopathy (TMA) characterized by severe hereditary ADAMTS13 (a disintegrin and metalloproteinase with thrombospondin type 1 motifs 13) deficiency caused by ADAMTS13 mutations. This rare autosomal recessive genetic disorder is often misdiagnosed as immune thrombocytopenia (ITP) or hemolytic uremic syndrome (HUS). Here, we report a 21-year-old male cTTP patient with a compound heterozygous ADAMTS13 mutation. The patient was admitted for acute thrombocytopenia, with a 5-year history of chronic thrombocytopenia and 1 month of renal dysfunction. Initially diagnosed with ITP, he was treated with immunosuppressive therapy, including glucocorticoids and intravenous immunoglobulin, which provided temporary relief but failed to prevent recurrent thrombocytopenia. Ultimately, cTTP was confirmed by the low ADAMTS13 0% activity and two heterozygous variants (c.1335del and c.1045C > T) in the ADAMTS13 gene, and the patient received prophylactic fresh-frozen plasma (FFP) infusions every 2–3 weeks regularly. Interestingly, the patient also exhibited elevated sC5b-9 levels during the acute phase, necessitating differentiation from HUS. This report highlights a cTTP caused by a compound heterozygous ADAMTS13 mutation, although its pathogenesis requires further investigation. Given the atypical clinical manifestations of cTTP, it is necessary to conduct ADAMTS13 activity and even genetic testing in patients with recurrent thrombocytopenia and end-organ damage.